2018
DOI: 10.1016/j.actpsy.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical time-to-contact error with two moving objects persists across different vertical separations

Abstract: When human observers estimate the time-to-contact (TTC) of more than one object there is an asymmetric pattern of error consistent with prioritizing the lead object at the expense of the trail object. Here, we examined TTC estimation in a prediction motion task where two objects moved along horizontal trajectories (5 or 7.5 °/s) that had different vertical separation, and thus placed specific demands on visuospatial attention. Results showed that participants were able to accurately judge arrival order, irresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The general overestimation of time intervals that we observed seems to be related to our specific stimulus settings. Here, short intervals (around 250–800 ms) were employed which are often overestimated (Benguigui et al, 2003 ; Bennett et al, 2018 ; Vicovaro et al, 2019 ). Remarkably, univariate fMRI‐results showed that, to some extent, activity in low‐level visual regions was tied to estimated motion trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…The general overestimation of time intervals that we observed seems to be related to our specific stimulus settings. Here, short intervals (around 250–800 ms) were employed which are often overestimated (Benguigui et al, 2003 ; Bennett et al, 2018 ; Vicovaro et al, 2019 ). Remarkably, univariate fMRI‐results showed that, to some extent, activity in low‐level visual regions was tied to estimated motion trajectories.…”
Section: Discussionmentioning
confidence: 99%